1999
DOI: 10.1034/j.1399-3003.1999.14b32.x
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis: inflammatory response to infection with Burkholderia cepacia and Pseudomonas aeruginosa

Abstract: Pulmonary colonization by Burkholderia cepacia in cystic fibrosis (CF) may be associated with enhanced deterioration of pulmonary function. This may be due to a more florid host inflammatory response than in colonization by Pseudomonas aeruginosa, leading to greater lung injury.Circulating markers of inflammation were determined during infective exacerbations and periods of clinical stability in an 18 month prospective study in adults with CF colonized by P. aeruginosa (n=41). B. cepacia (n=13) and in adults w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 12 publications
1
17
1
Order By: Relevance
“…However, in a study by Hendry et al significant reductions were observed in WCC, CRP, and pNEC following antibiotics. 18 IL-8, a powerful neutrophil chemoattractant, did not change in our study. A recent investigation did show a reduction in IL-8 following IV antibiotics.…”
Section: Discussionmentioning
confidence: 60%
“…However, in a study by Hendry et al significant reductions were observed in WCC, CRP, and pNEC following antibiotics. 18 IL-8, a powerful neutrophil chemoattractant, did not change in our study. A recent investigation did show a reduction in IL-8 following IV antibiotics.…”
Section: Discussionmentioning
confidence: 60%
“…cepacia complex is known to be a relevant pathogen in CF, at least in a subgroup of patients who develop a massive inflammatory response [20,21]. The prevalence of this group of pathogen was relatively low in our study making it difficult to assess the clinical relevance within this patient population.…”
Section: Discussionmentioning
confidence: 65%
“…Finally, measuring levels of host inflammatory markers may not provide an accurate prediction of future clinical outcome. A previous study did not find a difference in levels of blood cytokines between CF patients with P. aeruginosa and B. cepacia complex [22], despite a well-recognised increased pathogenicity of B. cepacia complex in clinical practice [28,29]. However, that study had smaller numbers of subjects and measured circulating inflammatory markers, which may not be as representative of inflammatory activity within the lung as those in bronchoalveolar lavage fluid or sputa.…”
Section: Discussionmentioning
confidence: 76%
“…The current study was designed to investigate whether adult CF patients who harbour transmissible P. aeruginosa strain MA demonstrate a more florid host inflammatory response than those who harbour sporadic strains of P. aeruginosa. Patients with chronic P. aeruginosa infection experience episodes of respiratory exacerbations that are associated with a decrease in lung function and a systemic inflammatory response, with increased levels of inflammatory markers, including TNF-a, NE/a 1 -antitrypsin complexes, IL-6, IL-8 and CRP [11,[22][23][24]. I.v.…”
Section: Discussionmentioning
confidence: 99%